2023
DOI: 10.21608/auej.2023.283035
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Survey on Examinees Identity Authentication in Online Distant Exams

Abstract: The COVID-19 pandemic has changed the lifestyle in global education systems in favor of more reliance on e-learning, which is believed to be a change that will continue. Exams are no exception as they are also moving towards online remote exams where examinees can take their exams at their remote locations. However, it is worth noting that it is still difficult to ensure that the full discipline of the exam session is administered remotely, as is the case for traditional exams that are conducted in the classro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Saleh et al [24] conducted a systematic survey on identity authentication methods for online exams, examining various techniques and technologies, their strengths, weaknesses and effectiveness. The authors found that while various identity authentication methods were available for online exams, there needed to be more than a one-size-fits-all solution.…”
Section: Related Workmentioning
confidence: 99%
“…Saleh et al [24] conducted a systematic survey on identity authentication methods for online exams, examining various techniques and technologies, their strengths, weaknesses and effectiveness. The authors found that while various identity authentication methods were available for online exams, there needed to be more than a one-size-fits-all solution.…”
Section: Related Workmentioning
confidence: 99%